(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2016)
Soil contamination by radionuclides, heavy metal, pesticides, among others, threatens ecosystems and human health. Environmental monitoring bodies and agencies need reference values for these contaminants in order to assess the impacts of anthropogenic activities on soil contamination. Quality Reference Values (QRVs) reflect the natural concentrations of contaminants in soils without anthropic interference and must be regionally established. The aim of this study was the determination of natural concentrations and quality reference values for U and Th in soils from Minas Gerais State, Brazil. A large variation of the natural activity concentration of these radionuclides in soil was observed. The QRV for U was 86.5 Bq kg-1 and 90.81 Bq kg-1 for Th. Statistical analysis showed that the two elements have a positive correlation with the clay and organic matter content in soil, and with the soil orders Ultisol and Inceptisol. Uranium shows a strong correlation with As, Sb, Se and Hg, while Thorium does not show correlation with any of the trace elements.